A Critique of the Bucket Classification of Journals: The ABDC List as an Example1. Issue 298 (8th April 2016) - Moosa, Imad A.
Abstract : Journal ranking is a hazardous endeavour even if it is based on objective criteria. Additional problems arise from the use of an opinion‐based bucket classification of journals. As a bucket classification system, the ABDC list encourages rent‐seeking and arbitrage whereby a researcher goes for the lowest‐quality journal within each bucket or moves to another bucket. The quality of research output should not be judged on the basis of a predetermined list. It would be beneficial if the Australian Business Deans Council list were abandoned for the same reasons that led to the abandonment of the Excellence in Research for Australia list.